Hammer Throw: the headache of the "entry" - Strelnitski, V. (Techniques Magazine, 2019)
The entry into the first turn is the most technically challenging and the most consequential phase of hammer throwing. The use of a rotating reference frame helps us understand the complex mechanics of this phase and derive technical recommendations for its execution. The byproduct of the article is the exoneration of the centrifugal force and other inertial forces from the unjust claims that they are "fictitious" and thus nonexistent.